Analisis Penggunaan Konjungsi Koordinatif pada Teks Opini dalam Laman IDN Times Edisi Januari 2025 sebagai Sumber Bacaan dan Informasi - Alya Nurul Rizky Athallah; Naelatul Fauziyah; Rizka Aulia Firdaus; Faridatun Nadiyah; Najlaa Ekadita Tiarso; Asep Purwo Yudi Utomo; Rossi Galih Kesuma; Faizal Arvianto (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to identify the use of coordinating conjunctions in opinion texts published on the IDN Times page in the January 2025 edition. It was motivated by the need to understand the correct use of conjunctions in opinion texts to improve the ability to capture the meaning of sentences and understand the overall content of opinion texts. The approach used in this analysis is a systematic data analysis technique. The process of analyzing the use of coordinating conjunctions includes several stages, including reading opinions from related pages, reviewing opinions on associated pages, filtering and simplifying data based on relevant theories, identifying conjunctions that appear, evaluating data, formulating analysis results, and presenting findings in a structured manner. This study focuses on the accuracy of the use of coordinating conjunctions and their effects in a sentence. This analysis aims to identify the use of coordinating conjunctions in opinion texts and analyze the impact of their use in the text. A total of 247 conjunctions were identified in the opinion texts, all of which were used correctly.